IMPLEMENTATION OF GUIDANCE AND COUNSELING PROGRAMS IN STUDENT LEARNING IN ELEMENTARY SCHOOLS - Niyang Ayu Firdiana; Sefina; Hanikah; Fikriyah (Ann Publisher, 2024)
It is very important to have a good understanding of guidance and counseling in the education of students in primary schools, especially with regard to teaching and learning activities in the classroom. The objectives of this article are to: a) Explain how the guidance and counseling program is implemented in elementary schools; b) Explain the role of teachers in implementing the guidance and counseling program; c) Explain teachers' efforts to implement student learning guidance; and d) Explain how guidance and counseling teachers communicate with parents about student learning outcomes. This research is categorized as field research, which uses a descriptive qualitative approach. Data collection methods used observation, in-depth interviews, and documentation. Data analysis uses qualitative analysis, which means that the data is described in words or sentences and then comes to a conclusion through the following steps:: a) data reduction; b) data presentation (data display), c) conclusion drawing (verification). The results of this study indicate that at SD Negeri 1 Kenanga there is already a counseling guidance program (BK) which includes student learning guidance services. The teacher as the executor of the guidance provider has provided learning guidance to students who are experiencing difficulties well.